Project management handbook - Kuster, Jürg (Management for professionals., 2015)
This practical handbook offers a comprehensive guide to efficient project management. It pursues a broad, well-structured approach, suitable for most projects, and allows newcomers, experienced project managers and decision-makers to find valuable input that matches their specific needs. The Project Management Compass guides readers through various sections of the book; templates and checklists offer additional support. The handbook's innovative structure combines concepts from systems engineering, management psychology, and process dynamics. This international edition will allow to share the authors' experience gained in many years of project work and over 2,000 project management and leadership seminars conducted for BWI Management Education in Zurich, Switzerland. This is an excellent handbook for practical project management in today's world. Prof. Dr. Heinz Schelle, Honorary Chairman of the GPM (German Project Management Association)The authors' many years in practical experience in setting up, implementing and managing projects shines through in this book. The book also reflects the current trend towards increased social competence. I am therefore pleased to recommend this book as a basis for certification in project management. Dr. Hans Knöpfel, Honorary President of the SPM (Swiss Project Management Association).- Resumé vydavatel